Simultaneous Combination of Electrocoagulation and Chemical Coagulation Methods for Medical Wastewater Treatment - Muharam, Salih; Yuningsih, Lela Mukmilah; Rahmah, Citra Ibdau (UI Scholars Hub, 2017)
Chemical coagulation, electrocoagulation, and combined electrocoagulation-chemical coagulation methods were used to reduce organic compound concentrations in medical wastewater. Some parameters in the methods were adjusted to optimize the process, including the applied current, distance between electrodes, number of electrodes, acid levels, coagulant type, and contact time. Chemical Oxygen Demand (COD) was used to indicate the total amount of organic compounds in the system. The results showed that the following conditions can be applied to achieve optimum results: 3 A of applied current, 4 pairs of electrodes, with 1 cm of distance between each electrode pair, a pH of 8, 1 g of polyaluminum chloride as the coagulant, and 3 hours of contact time. The optimum removal efficiency levels of total organic compound achieved via chemical coagulation, electrocoagulation, and the simultaneous combination of electrocoagulation-chemical coagulation methods were 41%, 62.51%, and 92.21%, respectively.